A comparison of actual playing time and duration of out of play in football leagues between Korean Professional League Division 1 (K.League) and England Premier League (EPL) - An, I. S.; Choi, H. J.; Park, T. S. (7th World Congress on Science and Football (WCSF), 2011, 2011)
This study was mainly to identify the situations in duration of out of play based on the duration of throw-in, duration of goal-kicks, type of attacking interruptions, foul characteristics, applicability of football pitch and coaches' playing styles. There were also purposes of this study that to compare the actual playing time(APT) and duration of out of play(DOP) between K-league and EPL. Methods Totally, 20 matches in K-league and EPL were compared that all matches were selected with reduced variance of external factors such as weather and home/away. A video analysis software (called, SportsCode) was used to collect the duration of out of play and actual playing time. As statistical determinations, the Mann-whiney U test and Independent sample T-test were used after the data collection. Results & Discussion The results of the comparisons of APT and DOP between K-league and EPL were shown as below; Firstly, a team per game played 25 minutes 58 seconds in mean (sd= 3' 23") in K-league and the mean of a team playing per game in EPL was 30 minutes 10 seconds (sd=5' 5"). Also, the DOP in K-league (21' 53"±3' 48") were 4 minutes 12 seconds in mean greater than EPL's (17' 40"±2' 47"). Secondly, there were significant differences of the frequencies comparisons on the DOP of throw-in, corner kicks, indirect free-kicks, goal-kicks, fouls, injuries substitutions and direct free-kicks between K-league and EPL(p<.05). Totally, there were both significant differences of frequencies and durations on the DOP that the factors were throw-in, indirect free-kicks, goal-kicks, fouls, injuries and substitutions(p<.05). Conclusion This study was not able to be considered the external factors of DOP, but it attempted to concern the internal factor of which the football audience could observes directly in the football pitch. Therefore, it is expected that the results of this study could aid to revise the problematic issues in K-league as well as the development of educational programs for coaches, athletes and referees.